Identification of the Transgene Integration Site and Host Genome Changes in MRP8-Cre/ires-EGFP Transgenic Mice by Targeted Locus Amplification - Wang, Guan; Zhang, Cunling; Kambara, Hiroto; Dambrot, Cheryl; Xie, Xuemei; Zhao, Li; Xu, Rong; Oneglia, Andrea; Liu, Fei; Luo, Hongbo R. (Frontiers in Immunology, 2022)
The MRP8-Cre-ires/EGFP transgenic mouse (Mrp8creTg) is popular in immunological and hematological research for specifically expressing Cre recombinase and an EGFP reporter in neutrophils. It is often crossed with other transgenic lines carrying loxP-flanked genes to achieve restricted gene knockout in neutrophils. However, due to the way in which the line was created, basic knowledge about the MRP8-Cre-ires/EGFP transgene in the host genome, such as its integration site(s) and flanking sequences, remains largely unknown, hampering robust experimental design and data interpretation. Here we used a recently developed technique, targeted locus amplification (TLA) sequencing, to fill these knowledge gaps. We found that the MRP8-Cre-ires/EGFP transgene was integrated into chromosome 5 (5q31.2) of the host mouse genome. This integration led to a 44 kb deletion of the host genomic sequence, resulting in complete deletion of Serpine1 and partial deletion of Ap1s1. Having determined the flanking sequences of the transgene, we designed a new genotyping protocol that can distinguish homozygous, heterozygous, and wildtype Mrp8creTg mice. To our surprise, crossing heterozygous mice produced no homozygous Mrp8creTg mice, most likely due to prenatal lethality resulting from disrupted Ap1s1 gene expression.